Kan-Lu-Hsiao-Tu-Tan, a traditional Chinese medicine formula, inhibits human neutrophil activation and ameliorates imiquimod-induced psoriasis-like skin inflammation. (10th January 2020) - Chiang, Chih-Chao; Cheng, Wei-Jen; Lin, Cheng-Yu; Lai, Kuei-Hung; Ju, Seanson-Chance; Lee, Chuan; Yang, Sien-Hung; Hwang, Tsong-Long
Abstract: Ethnopharmacological relevance: Kan-Lu-Hsiao-Tu-Tan (KLHTT) is a popular traditional Chinese medicine for treating various inflammatory diseases. Aim of the study: The aim of the present study was to investigate the anti-inflammatory effects of KLHTT on human neutrophils and its therapeutic potential in treating imiquimod (IMQ)-induced psoriasis-like skin inflammation. Materials and methods: Spectrophotometry, flow cytometry, and microscopy with immunohistochemical staining were used to evaluate superoxide anion generation, elastase release, CD11b expression, adhesion, and neutrophil extracellular trap (NET) formation in activated human neutrophils. Reactive oxygen species (ROS) and reactive nitrogen species in cell-free systems were measured using a multi-well fluorometer or a spectrophotometer. A psoriasis-like skin inflammation was induced in mice using the IMQ cream. Results: KLHTT suppressed superoxide anion generation, ROS production, CD11b expression, and adhesion in activated human neutrophils. In contrast, KLHTT failed to alter elastase release in activated human neutrophils. Additionally, KLHTT had an ROS-scavenging effect in the AAPH assay, but it did not scavenge superoxide anions directly in the xanthine/xanthine oxidase assay. Protein kinase C (PKC)-induced NET formation most commonly occurs through ROS-dependent mechanisms. KLHTT significantly inhibited phorbol 12-myristate 13-acetate, a PKC activator, inducing NET formation. Furthermore, topical KLHTT treatment reduced the area affected by psoriasis area and severity index (PASI) score and ameliorated neutrophil infiltration in IMQ-induced psoriasis-like skin inflammation in mice. Conclusions: Our data show that KLHTT has anti-neutrophilic inflammatory effects in inhibiting ROS generation and cell adhesion. KLHTT also mitigated NET formation, mainly via an ROS-dependent pathway. In addition, KLHTT reduced neutrophil infiltration and improved the severity of IMQ-induced psoriasis-like skin inflammation in mice. Therefore, KLHTT may prove to be a safe and effective psoriasis therapy in the future. Graphical abstract: Image 1